CIVIL-MILITARY RELATIONS Control and Effectiveness Across Regimes - Bruneau, Thomas C.; Croissant, Aurel (Lynne Rienner Publishers, 2019)
How does civilian control affect military effectiveness? Can a balance be achieved between the two? In-country experts address these questions through a set of rich comparative case studies. Covering the spectrum from democracies to authoritarian regimes, they explore the nexus of control and effectiveness to reveal its importance for national security and the legitimacy of both political order and the military institution.